Impairment of place navigation of rats in the Morris water maze by intermittent light is inversely related to the duration of the flash - Liu, Z; Turner, L F; Bures, J (Neuroscience letters, 1994)
The relative contribution of allocentric and egocentric orientation to place navigation was studied in Long-Evans rats trained in the Morris water maze in permanent light, permanent darkness or flickering light (1 Hz, flash durations 25, 100, 300, 500 and 800 ms). After 3 days of training (nine blocks of four trials), escape latencies were 38 and 7 s in the dark- and light-trained groups, respectively, and corresponded to the light-dark ratio in the flicker-trained groups. Shorter-than-predicted latencies in the 25- and 100-ms groups reflected visual persistence of approximately 200 ms. The difference between flickering light (100 ms) and permanent light performance during acquisition of place navigation to a new target was significantly smaller in rats previously trained in light than in naive animals. It is concluded that longer flash duration gives the animals more opportunities to locate relevant landmarks and to estimate their distance.
Keywords: krysa rodu Rattus; Animals; Space Perception; tma; vnímání prostoru; Darkness; Maze Learning; mužské pohlaví; zvířata; Male; bludiště - učení; Rats; světelná stimulace; Photic Stimulation